Catalytic CH Amination: A Reaction Now Accessible to Engineered Natural Enzymes1. Issue 27 (4th June 2014) - Mahy, Jean‐Pierre; Ciesielski, Jennifer; Dauban, Philippe
<x xml:space="preserve">Abstract</x> Catalytic CH aminations with natural enzymes have not been reported thus far. However, when a cytochrome P450 enzyme is modified by switching from an iron(III) to an iron(II) center and by mutating amino acids that are critical for the catalytic activity of this monooxygenase, this modified enzyme catalyzes the intramolecular CH amination of benzenesulfonyl azides.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>